2015
DOI: 10.1007/s12149-015-0952-z
|View full text |Cite
|
Sign up to set email alerts
|

A performance comparison of novel cadmium–zinc–telluride camera and conventional SPECT/CT using anthropomorphic torso phantom and water bags to simulate soft tissue and breast attenuation

Abstract: CZT camera has better physical performance and image quality with less artificial perfusion defects than conventional SPECT. CZT camera also has less breast attenuation than conventional SPECT. However, extracardiac soft tissue may degrade the superior performance of CZT camera, and attenuation correction methods are still needed to solve the attenuation issues in inferior and inferolateral myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 27 publications
2
27
0
1
Order By: Relevance
“…The lack of significant differences in the considered parameters along the range of count statistics explored, combined with the increased sensitivity of these systems (fourfold for the D530c to sevenfold for the D-SPECT) in comparison to a conventional Anger camera, 9,14 seems to indicate that there is still a possibility for a further reduction in the injected activity and/or the acquisition time, in order to improve patients' comfort and contain both patients' and operators' radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of significant differences in the considered parameters along the range of count statistics explored, combined with the increased sensitivity of these systems (fourfold for the D530c to sevenfold for the D-SPECT) in comparison to a conventional Anger camera, 9,14 seems to indicate that there is still a possibility for a further reduction in the injected activity and/or the acquisition time, in order to improve patients' comfort and contain both patients' and operators' radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, CNR values in our study are higher than those reported by Liu et al for the D530c (*3.8). 14 …”
Section: Contrast-to-noise Ratiomentioning
confidence: 99%
“…Liu et al used an anthropomorphic torso phantom and found that CZT had higher myocardial count sensitivity, better signal-tonoise ratio, and superior uniformity of overall myocardial tracer uptake compared to NaI; however, CZT was more susceptible to inferior and inferolateral attenuation with lower normalized uptake compared to the NaI camera in the anthropomorphic torso model to simulate a male patient. 20 Similarly, Herzog et al reported predominant artifacts in the right coronary artery territory in males. 21 In contrast, CZT performed better than the NaI camera in imaging anterior defects.…”
Section: Role For Ct Attenuation Correctionmentioning
confidence: 91%
“…21 In contrast, CZT performed better than the NaI camera in imaging anterior defects. 20 This phenomenon may be explained by the design of the CZT camera, since the pinhole collimator is closest to the linear source in the anterior position and furthest in the right lateral position.…”
Section: Role For Ct Attenuation Correctionmentioning
confidence: 99%
“…Compared with conventional NaI gamma cameras, the CZT gamma cameras have multiple advantages, such as improved spatial resolution, high energy resolution, and high sensitivity which reduces patients' discomfort and minimizes motion artifacts [37,40,41]. However, since the acquisition using the CZT cameras is performed by positioning gamma-ray detectors on the anterior and left lateral side of the thorax, the myocardial SPECT images show noticeable attenuation artifacts in the septal, inferoposterior, and posterolateral wall of the left ventricular myocardium [42]. The degree of attenuation artifacts in CZT images is markedly higher than in conventional NaI images (Figure 1).…”
Section: Ctac For Myocardial Spect Using Solid-state Gamma Camerasmentioning
confidence: 99%